Willingness to Communicate Orally: The Case of Iranian EFL Learners - Tavakoli, Elaheh; Davoudi, Mohammad (Journal of psycholinguistic research, 2017)
This study sets out to develop a questionnaire on willingness to communicate (WTC) orally specific to English as a Foreign Language setting. It also aims to investigate the effect of three independent variables of interlocutor, age and gender on the same construct of WTC orally. Exploratory factor analysis resulted in three dimensions to WTC, namely WTC with teacher, with classmate, and stranger. Also Cronbach’s alpha of .86 indicated a high internal consistency. Mixed between–within subjects analysis of variance was used to assess the impact of interlocutors, age and gender on participants’ WTC across the three WTC subscale scores. The results showed no interaction effect between any of pairs of variables but the main effect of interlocutor on WTC orally. The results are discussed in the context of language teaching and some pedagogical implications are suggested.